Implications of Urban Dog Ownership on Business Opportunities in Prague - Miškóciová, Simona (2025)
This thesis explores how urban dog ownership influences business opportunities in Prague. The main goal was to understand the expectations, habits, and emotional drivers of dog owners and translate them into practical insights for entrepreneurs. The research combined theoretical analysis with primary data collection through a structured questionnaire (N=222), analyzed using both quantitative (descriptive statistics, correlation tests) and qualitative (thematic coding) methods. The findings reveal a mature, emotionally engaged consumer segment with strong mid-range spending and high expectations around quality, personalization, and emotional connection. Market inefficiencies were identified in areas like grooming, training, and service accessibility. The study concludes with a set of strategic business recommendations and a future outlook on the evolving role of dogs in urban life, emphasizing their growing importance not only in households, but across local economies and community culture.